Pension benefit insurance and pension plan portfolio choice - Thomas F. Crossley; Mario Jametti (Center for Economic Studies and ifo Institute (CESifo), 2008)
Pension benefit guarantee policies have been introduced in several countries to protect private pension plan members from the loss of income that would occur if a plan was underfunded when the sponsoring firm terminates a plan. Most of these public insurance schemes face financial difficulty and consequently policy reforms are being discussed or implemented. Economic theory suggests that such schemes will face moral hazard and adverse selection problems. In this note we test a specific theoretical prediction: insured plans will invest more heavily in risky assets. Our test exploits differences in insurance arrangements across Canadian jurisdictions. We find that insured plans invest about 5 percent more in equities than do similar plans without benefit guarantees.
Keywords: G23; G11; C21; 330; Pensions; benefit guarantee; moral hazard; Pensionsfonds; Private Rentenversicherung; Garantie; Portfolio-Management; Moral Hazard; Kanada